THE EFFECTIVENESS OF REGIONAL REGULATION NO. 4 OF 2012 ON PUBLIC SERVICE LEVIES IN THE FRAMEWORK ORDER CREATING TRAFFIC ON THE ROAD SURYAKENCANA CITY OF BOGOR - yadi, Mul; Rudyantoro, Harry; Bahar, Ujang (DERECHTSSTAAT, 2015)
ABSTRACT Â Related to the implementation of the Regional Regulation (Perda) about the increase in parking rates at the edge of the road prone to congestion in the city of Bogor ratified and entered into force on July 2, 2012, The first location that imposed this tariff is the Way Suryakencana and Jalan Siliwangi Bogor and the second location is the application of The Government through the Department trials Traffic Transportation (DLLAJ) Bogor City gets a reaction from the people around Jalan Suryakencana. Enactment of the increase in parking rates at Jalan Bogor Suryakencana expected to reduce illegal parking of vehicles in the area, which has been causing congestion. With parking rates that have been enacted many road users who park their vehicles in multiple and indiscriminate. The method used in this study is empirical juridical approach. The study, based on an inventory of positive law, the discovery of the principles of law and legal discovery inconcretto, which include observation of empirical operationalization of law in society. The conclusion from this study is the basis of the application of the levy Parking Services Bank Public Road, especially in the city of Bogor is Law No. 28 of 2009 on Regional Taxes and Levies and Regional Regulation No. 4 of 2012. Implementation of Regional Regulation No. 4 of 2012 on Increase Rates Parking is not yet fully effective this is due to high payments also has not been matched with adequate services, the responsibility for the damage and loss still be a burden for the owner of the vehicle so that the functions and responsibilities of the government that deal with parking problems is questionable. Impact parking tariff policy to demand that any increase in the parking rate of 10 percent would result in a decrease in the use of parking of 0.7 -0.8 percent, increase use of public transport and cycling amounted to 3.71 percent of 0.9 percent. This figure is even greater in the short term, when applied can lead to a new increase in the elasticity to be about - 0.28., Where the parking lot reducing the length of parking time and reduce the amount of parking. Â Keywords: Regional Regulation, Rates Parking, Traffic Order